The Music is the evolution and development of the human race - Saybay Zorogastúa, Víctor (2018)
The music is the evolution and the development of the human race, It is an article that encapsulates and pretends to explain through scientific, philosophical and humanistic canones, the focus of this resounding organization that defines as a science, art and time in the context of civilization and the development of our own universe.